Use of eco-art education in supporting the establishment of sustainability competencies in basic education: an interventionist case study - Da Silva, Juliana Schmidt (Rhodes University, Faculty of Education, Department of Education, 2020)
Recent socioecological approaches in Environmental Education acknowledge the complexity of "real-world situations" , which include environmental problems. One response to the challenge of enabling people to develop sustainability is the key competencies in sustainability framework. It can be faced as a guide to planning Environmental Education actions. On the other side, art practices hold potential to expand learning in varied ways. Art can offer the strategies employed in learning processes directed to sustainability, constituting the field of eco-art education. This research aims to investigate the integration of the visions of the key competencies in sustainability and the eco-art education in an Environmental Education project at high school level. Horta and Gastronomia (Vegetable Garden and Gastronomy) is an extra-curricular activity which happens every year at IrmÃ£o Jaime Biazus high school in Porto Alegre, Brazil. It addresses food security and sustainability associating the garden, the kitchen and exploration of sustainability issues using eco-art strategies. Action research approach is used, defining two research cycles to explore the effectiveness of eco-art for the development of key competencies in sustainability. The first cycle focuses on the eco-art activities applied in Horta and Gastronomia (2017 group) while the second cycle deals with a post-project intervention designed to observe indicators of the sustainability competencies and further explore eco-art strategies. This study adds to the field of sustainability competencies by exploring teaching strategies through eco-art education. Insight into key competencies in sustainability is given by presenting the investigation of the group of students about a situation of their reality. The activities implemented, classified according to their objectives, are contextualized regarding the competencies and in learning sequences. This research also contributes to the development of the sustainability competencies framework by applying the theory to a basic education level, adapting the work originally proposed to higher education contexts.
Keywords: Environment (Art); Environmental education -- Brazil; Sustainable development -- Brazil; Education -- Curricula -- Brazil; Eco-art education